2006. Implementation of the T2 Biosystems T2Bacteria Panel in a Level-One Trauma Center, Safety Net Hospital. (26th November 2018) - Robinson, Caitlin; Jackson, Rebecca; Sauaia, Angela; Cohen, Mitchell
Abstract: Background: Rapid detection and identification of sepsis causing pathogens are critical for optimizing antimicrobial therapy to improve patient survival and reduce healthcare costs. The T2Bacteria Panel RUO is a molecular diagnostic allowing detection of Gram-negative Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii and Gram-positive Staphylococcus aureus and Enterococcus faecium within a few hours. The purpose of our study was to determine the feasibility and efficacy of the T2Bacterial Panel RUO in an Emergency Medicine (ED) and Surgical Intensive Care Unit (SICU) setting. Methods: An IRB-approved, prospective, observational study was implemented at a Safety-Net, Level One Trauma Center in Denver, Colorado. Patients were enrolled who received an order for a blood culture from the ED or SICU. Patients who had blood drawn for cultures had a concurrent draw for testing with a T2Bacteria Panel RUO. Results: Sixty-six patients are included in the present interim analysis. Mean patient age was 51 years old (19–84), 36% were female, 86% Caucasian (34% Hispanic/Latino), and 74% of patients were enrolled upon presentation to the ED, 13% from the SICU, and 15% from the wards. 90% of blood sampling (culture and T2Bacteria) was done from peripheral stick while 7% were from the initial stick of a peripheral IV and 2% obtained from an indwelling catheter. 85% of blood cultures were negative. Of the 56 patients with negative blood culture, 53 had concordant negative T2Bacteria results, providing a specificity of 94.6%. 10 patients had positive blood cultures (15%) for T2Bacteria Panel RUO targets. Interestingly, only five of these (50%) had concordant positive T2Bacteria testing. Examining the discordant samples, all (5) blood culture positive, T2Bacteria negative were found to have clinically false-positive blood cultures. T2Bacteria positive samples were distributed as follows: two E.coli, one S. aureus, one K. pneumoniae, and one P. aeruginosa . No detections were made for E. faecium or A. baumannii. Conclusion: In this interim analysis, T2Bacteria Panel RUO provides feasible rapid diagnostics for ED and surgical ICU settings with a high specificity and much shorter time to result when compared with gold standard blood cultures. Disclosures: C. Robinson, T2 Biosystems: Research Coordinator for funded study from T2 Biosystems, Research support. R. Jackson, T2 Biosystems: Research Assistant for funded study from T2 Biosystems, Research support. M. Cohen, T2 Biosystems: PI on study being funded by T2 Biosystems, not paying for any part of salary, Research support.